Government Supervision Mode Selection in the Promotion Period of Prefabricated Construction Using Evolutionary Game. (9th June 2020) - Jing, Shuwei; Zhang, Zhuangyi; Yan, Junai
Abstract : Aiming at the speculative behavior of some developers who seek private interests in the promotion period of prefabricated construction, this research combines the actual situation, objectively and reasonably determines the parameters in the model, and builds an evolutionary game model to study the choice of government supervision mode in different situations, from the perspective of government supervision. The results showed that the choice of government supervision mode has great connection with the probability of identifying developers' speculative behavior when the government adopts node supervision. When the probability is greater than the developers' speculative value, the government will choose node supervision, while the developers will not adopt speculative behavior. Conversely, there will be a periodic behavior pattern in the evolutionary system, and the choice of government supervision mode is related to the value of each parameter. At the same time, the minimum probability of identifying speculative behavior that keeps the optimal situation stable is obtained. On this basis, the paper takes a practical case to discuss the influence of different parameter variations on the choice of government supervision mode and makes numerical simulations; then it puts forward some specific suggestions for government to restrain the speculative behavior of developer.